MODEL FORMAT ASESMEN ALTERNATIF UNTUK GURU SEKOLAH DASAR DI BACAN KABUPATEN HALMAHERA SELATAN (Suatu Tinjauan Teoritik dalam pelaksanaan Kurikulum 2013) - Hamid Garwan (PEDAGOGIK, 2014)
The purpose of this theoretical study is to investigate alternative model assessment (portfolios, verbal presentations and debates, interviews and conferences, laboratory skills checklists, and evaluation of its own evaluation of paired peer evaluation) in learning in elementary school. Alternative assessment is defined as the use of non-traditional approach to assess the performance or student learning outcomes. Besides alternative assessment may also be referred to the authentic assessment or performance assessment. Alternative assessment is a new development of traditional assessment. In other words, alternative assessment does not eliminate the role of traditional assessment. Asessmen this alternative to be a solution for elementary teachers in assessing students' attitudes while in the learning environment. Kata kunci: Assesmen Alternatif, Elementary school Teacher